2018
DOI: 10.1021/acsmacrolett.8b00106
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Luminescent Triptycene-Based Polymers

Abstract: A series of chiral fluorescent polymers containing optically active triptycene units in the main chain were synthesized via Sonogashira–Hagihara coupling copolymerizations of (R,R)- or (S,S)-2,6-diethynyltriptycene with a range of diiodoaryls. Their optical and chiroptical properties were investigated under various solution conditions. We observe that these polymers emitted circularly polarized light owing to the chiral triptycene framework with a handed twisted rigid structure, and the fluorescence colors cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…For 36d , just six repeating units were needed to form stable helix with the help of the hydrogen bonds between the pendant amino groups. This group also reported polymerization of thiophene and triptycene with axial chirality to afford optically active copolymers 37 and 38 with blue and green CPL 62 . Hara et al reported linear ( 39 ) and hyperbranched ( 40 ) PThs‐bearing binaphthol (BINOL) as chirality‐inducing pendant groups 63 .…”
Section: Chirality In Polythiophenesmentioning
confidence: 99%
See 1 more Smart Citation
“…For 36d , just six repeating units were needed to form stable helix with the help of the hydrogen bonds between the pendant amino groups. This group also reported polymerization of thiophene and triptycene with axial chirality to afford optically active copolymers 37 and 38 with blue and green CPL 62 . Hara et al reported linear ( 39 ) and hyperbranched ( 40 ) PThs‐bearing binaphthol (BINOL) as chirality‐inducing pendant groups 63 .…”
Section: Chirality In Polythiophenesmentioning
confidence: 99%
“…This group also reported polymerization of thiophene and triptycene with axial chirality to afford optically active copolymers 37 and 38 with blue and green CPL. 62 Hara et al reported linear (39) and hyperbranched (40) PThs-bearing binaphthol (BINOL) as chirality-inducing pendant groups. 63 The hyperbranched PTh (40) exhibited clear CD bands in the absorption region of the PThs main chain (350-550 nm), whereas linear PTh (39) only presented CD band before 400 nm.…”
Section: Chirality Introduced By Substituents With Planar or Axial Chiralitymentioning
confidence: 99%
“…Organic materials have emerged as promising candidates owing to their easy processing, tunable chiral centers, and excellent photophysical properties 25 27 . Over the past few years, a lot of organic materials have been reported to exhibit CPL activity by combining the chiral units and the luminescent molecules via covalent bonds, such as transition metal complex 28 , 29 , small organic molecules 30 , 31 , and conjugated polymers 32 , 33 . However, they usually suffer from the relatively low luminescence dissymmetry factor ( g lum ), which quantifies the asymmetry degree of emission in left- and right-circularly polarized light.…”
Section: Introductionmentioning
confidence: 99%
“…A tentative assignment of the enantiomer elution order of Tripty-NO2 was carried by ECD empirical correlation, using the enantiomers of Tripty-I2 as references of known stereochemistry. 30 At shorter wavelengths, the ECD analysis showed a strict analogy between the more retained (S,S)-enantiomer of Tripty-I2 on the Chiralpak IG CSP and the less eluted enantiomer of Tripty-NO2 on the Chiralpak IB-U CSP (Figure 4). Nevertheless, in the 350-to 260-nm wavelength region, a substantial difference in ECD profiles was noted.…”
Section: Absolute Configuration Assignmentmentioning
confidence: 95%